Evaluación del efecto de sustancias homeopáticas sobre la etapa inicial de crecimiento de plantas de pimiento (Capsicum annuum) y el desarrollo in vitro DE Phytophthora capsici. - Jirón Giler, Jessica Isabel (2018)
Agrohomeopathy is based on the use of substances in infinitesimal dilutions to regulate physiological processes in plants and protect against the attack of pathogens that cause diseases. In the present work, the general objective was to evaluate the different homeopathic substances such as Silicea terra, Natrum muriaticum and Phosphoric acid in centesimal dilutions of 7C and 31C on physiology stages of germination and emergence in pepper (Capsicum annuum), and the in vitro growth of Phythopthora capsici causing the disease known as late blight in pepper. The different treatments were established under a completely randomized design with three repetitions and a control. In the germination and emergence stages, the percentage and growth rate were evaluated, morphometric variables such as length of radicle, length of stem, fresh and dry biomass. The homeopathic substances positively influenced the development of pepper plants being the best treatments in the germination stage Phosphoricum acidum 31 C that presented the longest root length with 4.77 cm, Silicea terra 7C showed the greatest growth of stem length with 3.77 cm and the highest fresh weight with 45.00 mg, Natrum muriaticum 31C obtained the highest dry weight with 5 mg. In emergency the homeopathic substance Natrum muriaticum 7C presented greater length of radicle with 8,30 cm and greater length of stem with 4,33 cm, Natrum muriaticum 31 C obtained the highest fresh weight of root with 22,00 mg, while, Natrum muriaticum 7C obtained a dry weight of 3.33 mg, the highest value of fresh weight of stem was Silicea terra 7C with 93.67 mg and Phosphoric acid with a dry weight of 8.00 mg. During the in vitro stage it was observed that Silicea terra 7C had the lowest number of chlamydospores with the highest percentage of inhibition, 55.97% and the smallest diameter with 85, 17 micrometers. The homeopathic improve the development of the pepper and infer in the development of the fungus, depending on the dynamisation or dilution used and the stage of development of the pepper. Key words: Homeopathic substances, dilutions, physiological stages, pathogens, in vitro.